Epidemiological patterns of animal bites in the Babol County, North of Iran - Ghaffari-Fam, Saber; Hosseini, Seyed Reza; Daemi, Amin; Heydari, Hassan; Malekzade, Rahim; Ayubi, Erfan; Nikbakht, Hossein Ali (Journal of acute disease, 2016)
To describe the current situation of animal bites in the Babol County, North of Iran. This was a cross-sectional study based on recently collected data of 3798 victims bitten (656 females and 3142 males) from 2010 to 2014 in the Health Center of Babol, Iran. The interest variables in the study included demographic variables, characteristics of animal, some of the time patterns, and some clinical patterns provided to victims. The average age of victims was (33.68 ± 17.23) years. The age group with the max proportion (for males, 32.1%; for females, 26.2%) of bites occurred in 18–30 years old group for males and 30–45 years for females. The ratio of male victims to female ones was 4.78. In terms of place of incident, 2502 (65.9%) cases of animal bites occurred in rural areas. Dogs and cats were the most dominant biters with 3340 (87.9%) and 395 (10.4%) bites, respectively. For the kinds of biters, 3643 (95.9%) were pets, 133 (3.5%) were strays and 22 (0.6%) were wild animals. Most of the lesions were on shoulder as well as upper organs (46.9%) and lower organs (41.0%), respectively. Since the average age of the subjects with injuries on the head and upper organs was lower than that of victims with other organs injured and since that pet dogs were the major biter, structured monitoring programs that focus on specified target groups in collaboration with other organizations are essential to control the animal bites.